Millennium Developmental Goal and Child Survival: Bangladesh perspective - Begum, Tamanna (Journal of Shaheed Suhrawardy Medical College, 2012)
In September 2000, meeting at the United Nation (UN) Millennium summit, the world's leaders agreed to remarkable document, the Millennium Declaration1,2,3. The Millennium Developmental Goals (MDGs) agenda were adopted by the world leaders reaffirmed their share duty to "All the world's people, especially the most vulnerable and in particular, the children of the world, to whom the future belongs." They subsequently pledged to set a specific goals, the MDGs, that focus their collective efforts in the coming year as they undertake the challenges of poverty reduction and sustainable development1,4 DOI: http://dx.doi.org/10.3329/jssmc.v1i1.12170 Journal of Shaheed Suhrawardy Medical College Vol.1, No.1, December 2009 p.18-21